Elaboración de hojuelas glaseadas sin gluten de la pulpa del fruto Artocarpus altilis (pan de árbol) - Rios Sinacaisiva, Jefferson (2022)
The objective of the research work was to determine the technological parameters in the preparation of gluten-free glazed flakes from the pulp of the fruit of Artocarpus altilis (Tree bread) using aguaje oil as a source of vitamin A and ascorbic acid (vitamin C) with the purpose of enriching the product. For the elaboration of the gluten-free glazed flakes, the quantitative methodology of the experimental type was used with randomized management of the variables that are divided into two factors F1: 50% concentration of tree bread flour and F2, type of oil (oil of aguaje and fish oil as a source of vitamin A. To make the flakes, a convection temperature of 65 ° C was used for 30 minutes and toasted for 5 minutes at 90 ° C, to then be glazed manually. of gluten, the following physicochemical analyzes were carried out, giving the following results: Moisture 6.66%, Fiber 4.14%, Carbohydrates 79.12%, Fat 5.80% as well as mineral analyzes, Vitamin C 917.86mg, Vitamin A (2984mg / 100g) , Iron 1.82mg, Calcium 18mg, Magnesium 4mg, Phosphorus, 30mg, Sodium 25, Potassium 1.70mg Microbiological analyzes of the Sanitary Standard according to Ministerial Resolution No. 451-2006 / MINSA indicate that gluten-free flakes of The pulp of the Artocarpus altilis fruit (tree bread), are suitable for human consumption, with respect to the sensory test, 75 semi-trained judges were used whose data obtained were processed and analyzed applying non-parametric tests using the SPSS version 25 software.